Effect of Helicobacter pylori eradication on treatment of gastro-oesophageal reflux disease: a double blind, placebo controlled, randomised trial. (14th January 2004) - Wu, J C Y; Chan, F K L; Ching, J Y L; Leung, W-K; Hui, Y; Leong, R; Chung, S C S; Sung, J J Y
Abstract : Background: The role of Helicobacter pylori eradication in the management of gastro-oesophageal reflux disease (GORD) is controversial. We hypothesised that H pylori eradication leads to worsened control of reflux disease. Methods: Consecutive patients with weekly reflux symptoms were prospectively recruited for endoscopy and symptom evaluation. Patients were enrolled if they had H pylori infection and required long term acid suppressants. Eligible patients were randomly assigned to omeprazole triple therapy ( Hp E group) or omeprazole with placebo antibiotics ( Hp + group) for one week. Omeprazole 20 mg daily was given for eight weeks for healing of oesophagitis and symptom relief. This was followed by a maintenance dose of 10 mg daily for up to 12 months. The primary study end point was the probability of treatment failure within 12 months, which was defined as either incomplete resolution of symptoms or oesophagitis at the initial treatment phase, or relapse of symptoms and oesophagitis during the maintenance phase. Predictors of treatment failure were determined by Cox's proportional hazards model. Results: A total of 236 GORD patients were screened and 113 (47.9%) were positive for H pylori ; 104 (92%) patients were included in the intention to treat analysis (53 in the Hp E group and 51 in the Hp + group). Thirty one patients (30%) had erosive oesophagitis at baseline. H pylori was eradicated in 98% of the Hp E group and in 3.9% of the Hp + group. Overall, 15 patients (28.3%) in the Hp E group and eight patients (15.7%) in the Hp + group had treatment failure. The 12 month probability of treatment failure was 43.2% (95% confidence interval (CI) 29.9–56.5%) in the Hp E group and 21.1% (95% CI 9.9–32.3%) in the Hp + group (log rank test, p = 0.043). In the Cox proportional hazards model, after adjustment for the covariates age, sex, erosive oesophagitis, hiatus hernia, degree of gastritis, and severity of symptoms at baseline, H pylori eradication was the only predictor of treatment failure (adjusted hazard ratio 2.47 (95% CI 1.05–5.85)). Conclusion: H pylori eradication leads to more resilient GORD.